Adult Mobility, Celebrations of Ancestors, and Mandates to Youth: Community Ties between Bolivia and Argentina (Andamios, Revista de Investigación Social, 2025)
I address the way in which practices of mobility and spirituality enroot, reinforce and challenge communitary ties among the Andean population that inhabits a location of the province of Buenos Aires, Argentina. I focus on expressions of the communitary in the periodic displacements of adults to their places of origin, in the cult to the ancestors and predecessors, and in the expectations towards the descendants. Through this characterization, I seek to comprehend diverse and evolving ways of projecting collective continuity and sustaining ties between settlements defined as Indigenous communities in Bolivia and a peri-urban neighborhood in Buenos Aires located more than 2000 km away.
Keywords: Mobility; celebrations; generations; communitary ties; continuity-discontinuity